2014
DOI: 10.1002/jcph.409
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis comparing the efficacy of entecavir and tenofovir for the treatment of chronic hepatitis B infection

Abstract: The efficacy of entecavir and tenofovir in patients with chronic hepatitis B virus (HBV) is inconsistent. To address this issue, we conducted a meta-analysis based on a current review of the literature addressing the efficacy and safety of entecavir and tenofovir. Electronic databases were searched through June 2014 for relevant clinical trials. We included 2 randomized controlled trials, 2 prospective cohort studies, and 7 case-control studies that included 1,656 patients. In the entecavir group, 842 of 992 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
5
21
0
4
Order By: Relevance
“…[12][13][14][15] In a meta-analysis of 11 studies comparing ETV and TDF in 1300 patients, no statistically significant differences were found between these agents for renal safety or hypophosphatemia over approximately 18 months. 16 However, renal toxicity (defined as a confirmed change in serum creatinine of 0.5 mg/dL from baseline, a decrease in creatinine clearance [CrCL] <50 mL/min and/or serum phosphorus <2 mg/ dL) was observed in approximately 8% of patients in a trial that followed 280 patients receiving TDF for 240 weeks. 17 Table 2 shows the safety results in clinical practice in different studies.…”
Section: Safetymentioning
confidence: 99%
“…[12][13][14][15] In a meta-analysis of 11 studies comparing ETV and TDF in 1300 patients, no statistically significant differences were found between these agents for renal safety or hypophosphatemia over approximately 18 months. 16 However, renal toxicity (defined as a confirmed change in serum creatinine of 0.5 mg/dL from baseline, a decrease in creatinine clearance [CrCL] <50 mL/min and/or serum phosphorus <2 mg/ dL) was observed in approximately 8% of patients in a trial that followed 280 patients receiving TDF for 240 weeks. 17 Table 2 shows the safety results in clinical practice in different studies.…”
Section: Safetymentioning
confidence: 99%
“…With regard to drug safety, some reports indicate that patients taking tenofovir may develop nephrotoxicity [6,7]. Two recent meta-analysis studies yielded inconsistent results, especially in comparisons of virological responses (VR) [8,9]. Güzelbulut et al found that entecavir and tenofovir are similarly effective in nucleos(t)ide (NA) -naive CHB patients with high viraemia ( 6 log copies/mL in hepatitis B e antigen (HBeAg)-positive patients or 5 log copies/mL in HBeAg-negative patients) after 48 weeks of therapy [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta‐analysis of 11 studies comparing ETV and TDF in 1300 patients, no statistically significant differences were found for renal safety or hypophosphatemia between the two treatments over approximately 18 months of treatment 5 . TAF is being evaluated in 2 ongoing randomized, double‐blind, phase 3 studies including 426 HBeAg(‐) and 875 HBeAg(+) patients with CHB.…”
Section: Safetymentioning
confidence: 99%